Pelatihan Copy Writing Berbahasa Inggris Pada Pelaku Usaha Smart Visa Bali - I Dewa Ayu Devi Maharani Santika; Komang Dian Puspita Candra; Anastasya Purnamaliana (Universitas Lancang Kuning, 2023)
Community Service Activities are carried out at the Smart Visa Bali Office. This office operates in the field of immigration services. Immigration is a very important thing in the world of tourism, especially Bali which is a destination for foreign tourists. In introducing their business, business actors only use conventional promotion methods, namely word of mouth, so not many consumers know about the existence of this office. Seeing this, the community service implementation team designed a work program to introduce businesses widely, including training and mentoring activities that aim to provide new knowledge for Smart Visa Bali business actors in conducting online promotions. The results of this activity show positive progress for partners. The participants can understand the training material independently by creating promotional content on Instagram using copy writing techniques that have been taught and applied to the Canva application. After the online promotion on Instagram social media was carried out, there was a change in the number of consumer visits to the Bali Smart Visa Office.